Nonpneumatic anti-shock garment utilization for obstetric hemorrhage management and its predictors among obstetric care providers in Ethiopia: a systematic review and meta-analysis - Eyob Shitie Lake; Mulat Ayele; Gizachew Yilak; Befkad Derese Tilahun; Besfat Berihun Erega; Alemu Birara Zemariam; Getinet Kumie (BMC, 2024)
Abstract Introduction Non-pneumatic Anti-Shock Garment (NASG) is a lightweight, reusable first aid compression device that squeezes blood from the lower extremities and centralizes blood circulation to vital organs of the body. Postpartum hemorrhage followed by severe preeclampsia/eclampsia is the leading primary cause of maternal death (A reduction in extreme maternal adverse outcomes and faster recovery from shock are more likely to occur with earlier NASG intervention. The median blood loss reduced by half when the NASG was used for obstetric hemorrhage management, which was associated with significantly reduced maternal mortality among the most severe cases. Objective To estimate the pooled prevalence of NASG utilization and its predictors in Ethiopia. Methods Appropriate and comprehensive searches of PubMed, MEDLINE, EMBASE, Google Scholar, HINARI, and Scopus were performed. The electronic literature search was last performed on November 18/2023. All observational study designs were eligible for this SRMA. All cross sectional studies reporting the prevalence/proportion of NASG utilization for obstetric hemorrhage management among obstetric care providers and associated factors were included in this SRMA. Primary studies lacking the outcome of interest were excluded from the SRMA. The extracted Microsoft Excel spreadsheet data were imported into STATA software version 17 (STATA Corporation, Texas, USA) for analysis. A random-effects model was used to estimate the pooled prevalence of NASG utilization among obstetric care providers in Ethiopia. The Cochrane Q-test and I2 statistics were computed to assess the heterogeneity among the studies included in the SRMA. Result A total of 1623 articles were found by using our search strategies and seven studies comprising 2335 participants were ultimately included in the SRMA. The pooled prevalence of NASG utilization for obstetric hemorrhage in Ethiopia was 43.34% (95% CI: 35.25, 51.42%). The findings of this subgroup analysis by sample size showed that the pooled prevalence of NASG utilization for obstetric hemorrhage was greater in studies with sample sizes of less than the mean sample size (48.6%; 95% CI: 32.34, 64.86%). Receiving training (AOR = 3.88, 95% CI: 2.08-5.37), having good knowledge (AOR = 1.99, 95% CI: 1.28-3.16), positive attitude (AOR = 2.16, 95% CI: 1.62-2.75) and having available NASGs in the facility (AOR = 4.89, 95%CI: 2.88-8.32) were significantly associated with the use of NASGs for obstetric hemorrhage management. Conclusion The level of NASG utilization for obstetric hemorrhage in Ethiopia is low. Receiving training, good knowledge, positive attitudes and availability of NASG were significantly associated with the utilization of NASG. Therefore, policy makers and other stakeholders should emphasize enhancing the knowledge and attitudes of obstetric care providers through continuous support and training. At the same time, they should work strictly in providing devices for all the health facilities.